STORAGE OF PLANT-BREEDING FORMS OF UTERINE ROOT CROPS OF CARROT SOWING - Хареба, В. В.; Хареба, О. В.; Позняк, О. В. (Scientific Progress & Innovations, 2013)
The modified method of storage of uterine root crops of plant-breeding forms of sowing carrot was considered; in its basis is reduction of root crops’ losses during winter storage and receipting of high-quality stock seed from the set combinations in the process of plant-breeding work. The considered modified method of storage of uterine carrot seed directly in the field is perspective for development in research institutions and seed farms in areas of the Northern Forest and Woodlands of Ukraine.